A post COVID-19 pandemic exploration of teaching strategies, attitudes, and values of Southern California community college faculty - Abril, Mari Elizabeth (My University, 2025)
On March 11, 2020, the COVID-19 virus unexpectedly became a global pandemic, forcing the World Health Organization (WHO) to take dramatic action to prevent the spread of the virus and disrupt education forever. According to the Centers for Disease Control and Prevention, educational institutions were quarantined to avoid spreading the virus, forcing students and faculty to move to fully online instruction. The forced transition to fully online instruction was hard for many people. Students stopped coming to class, faculty chose to retire or leave altogether, and colleges struggled to provide services to students and faculty. Further impacting faculty and adult learners were the unforeseen emergencies and crises during the pandemic, including employment and economic loss, displacement, eviction, homelessness, loss of family members due to COVID-19, and medical emergencies (Walker, 2021). Closing campuses and moving to remote learning caused a spectrum of psychological consequences, including fear, loneliness, overthinking, sleeplessness, and stress, giving rise to a heightened sense of uncertainty (Zhai & Du, 2020). All forms of in-person participation, like graduations, public forums, athletic competitions, and social organizations, were also canceled, raising concerns about how communities and leaders perceived the campus and its role as town-gown relations shifted (Bristow, 2016). Faculty who continued teaching during this challenging time needed to take extra steps to maintain communication, collaboration, and students' emotional engagement with the learning community. This qualitative study explored the experiences of community college faculty in Southern California who taught during the COVID-19 pandemic. It examined how faculty participants adapted their teaching methods, attitudes, and educational values in response to the sudden transition to fully online instruction. Additionally, it included what new technologies faculty used in their classes and their perspectives on teaching evolved during this unprecedented shift as well as the future of online education. Findings from the two research questions revealed that faculty adapted to online teaching by using new technology and implementing strategies to engage students in their online classes better. They updated their syllabi with online etiquette, mental health resources, and digital tools. Many allowed late work and practiced holistic grading, valuing participation and improvement over traditional grading. Faculty used platforms like TechConnect Zoom and Canvas to increase interaction and foster connectivity in a distance education environment. The research findings also indicated that while faculty participants' core values remained steady, their attitudes and teaching philosophies shifted significantly during the pandemic, especially with those who had never taught online. Faculty became more empathetic and flexible by prioritizing student well-being and adapting their teaching practices to address new challenges such as student anxiety, isolation, and access to technology. The transition to online education prompted many faculty to innovate and reconsider their approaches to inclusivity and support for students. Despite ongoing tensions about teaching modalities, faculty maintained high standards and a commitment to professional development, demonstrating resilience and a renewed focus on understanding students' lives beyond the classroom. Higher education has changed, become more student-centered, innovative, and online. College faculty are teaching more online and hybrid classes while new polices address distance education, generative artificial intelligence, digital literacy, and access to resources. Ongoing professional development is essential for faculty to stay current and adapt to these changes. The research also revealed several key topics that merit further investigation to deepen the understanding of faculty, students, and institutional experiences in the post-pandemic era. These topics included disciplinary differences in teaching practices, variations in faculty adaptation, post-pandemic student retention and success, equity impacts related to gender and race, student adaptation to teaching changes, post-pandemic administrative and staff work changes, campus climate and faculty engagement, theoretical perspectives on educational change, evolution of learning paradigms, faculty employment patterns, shared governance and faculty voice, and teaching modality and student success.
Keywords: COVID-19; Faculty; Strategies; Values; Innovations; Community college; Southern California